A study on "The factors that influence retirement planning behaviour among working individuals at Rembau, Negeri Sembilan"/ Norlida Alias - Alias, Norlida (Faculty of Business and Management, 2012)
The title of this research is "The Factors that Influence Retirement Planning Behavior among Working Individuals at Rembau, Negeri Sembilan ". The first objective of this research is to identify the main factor that influencing retirement planning behavior among working individuals at Rembau, Negeri Sembilan. The second objective is to determine the significant relationship between factors and retirement planning behavior among working individuals at Rembau, Negeri Sembilan. There are four independent variables involve in this research which are Knowledge of Retirement Planning, Goal Clarity, Potential Conflict on Retirement and Attitude of Retirement Planning. For the dependent variable is about the Retirement Planning Behavior. In order to achieve this research, the hypothesis focuses on the objective to identify whether have the significant relationship between Knowledge of Retirement Planning, Goal Clarity, and Potential Conflict on Retirement and Attitude of Retirement Planning toward Retirement Planning Behavior. In gathering the data, 200 set of questionnaires is distributed to working individuals at Rembau, Negeri Sembilan. Only 126 set of questionnaires was return back with answered. The reliability test, frequencies analysis, Pearson’s correlation and regression method was used for data analysis. The result shows all the variable are positive but weak and one variable which is Attitude toward Retirement Planning has the higher value in weak positive significant relationship with the Retirement Planning Behavior. The other three variables which are Knowledge of Retirement Planning, Goal Clarity, and Potential Conflict on Retirement have very weak positive significant relationship with the Retirement Planning Behavior.